Thermal Ablations for Colorectal Liver Metastases - Gennaro, Nicolò; Mauri, Giovanni; Varano, Gianluca Maria; Monfardini, Lorenzo; Pedicini, Vittorio; Poretti, Dario; Solbiati, Luigi Alessandro (Digestive Disease Interventions, 2019)
Approximately 25% of colorectal cancers patients will develop hepatic metastases in the course of their disease. Surgical resection of hepatic metastases remains the first treatment choice for these patients, when feasible. However, only approximately 30% of metastatic lesions are resectable at the time of diagnosis. Thermal ablations have played an increasing role over the last few decades in the palliative and curative setting of colorectal liver metastases (CRLMs) in nonsurgical candidates with a liver-predominant disease. Several different techniques have been used to perform image-guided thermal ablations in the liver, including radiofrequency ablation, microwave ablation, cryoablation, and laser thermal ablation. We review the current ablation techniques, image-guidance modalities, indications, and debated topics of image-guided thermal ablation in CRLMs. Moreover, recent results from clinical trials are discussed along with future trends in liver thermal ablations.
Keywords: liver; thermal ablation; colorectal metastasis